Isolation and Purification of Amylase from Serum of Patients with Pancreatitis and Comparing the Biochemical Properties with Amylase Purified from Healthy People - Abdulhakeem D. Hussein; Manal Q. Mohammed; Hajer Hussein; Hajer A. Mejbil (مجلة مركز بحوث التقنيات الاحيائية, 2022)
Back Ground: Amylases are a group of enzymes that hydrolyze starch into simple sugars. Amylase is secreted in the human body from saliva and the pancreas. Abnormal levels of the enzyme amylase indicate pancreatitis. Enzyme purification eliminates various proteins and other forms of biomolecules while restoring the majority of enzyme activity.